INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE AND ORGANIZATION CULTURE TOWARD EMPLOYEE SATISFACTION A CASE STUDY AT PT XYZ (CONSULTING COMPANY) - Norman Yachya, S.T., M.M., M.BA., Norman Yachya, S.T., M.M., M.BA. (issn 1978-6573, 1978)
The main purpose of this research paper is to study the significance of transformational leadership and organization culture in relation with Employee satisfaction at PT. XYZ. The study is based on quantitative data of 100 respondents of PT. XYZ employees from total of 307 employees, which cover all of PT. XYZ offices such as Jakarta, Bandung, Semarang, Surabaya, Bali, Medan, Palembang, Makassar, and Balikpapan. The conclusion that organization culture is the most influences factor on employee satisfaction followed by transformational leadership. Both factors have positively influenced on employee satisfaction. The implication of this research, that PT. XYZ should consider both factors of organization culture and transformational leadership in order to provide higher job satisfaction of employees. Keywords: Transformational Leadership, Organization Culture, and Employee Satisfaction.